The Effect of Promotions and Buying Interest on Increasing Product Sales Volume at PT. Indosat TBK Manado Branch - Tuju, Kezia; Tonny, Tonny; Maringka, Maringka; Mantur, Mercy (Formosa Journal of Applied Sciences, 2024)
The aim of this study is to ascertain how buying interest and promotions affect the volume of products sold at the PT. Indosat Tbk Manado Branch. The research approach makes use of quantitative techniques. 75,910 Indosat users in Manado City as of July 30, 2021, make up the study's population. Using the Slovin formula method, the author calculated the sample size, which came out to be 100 respondents. The regression equation is as follows, based on the research findings: Y = 2.140 + 0.417X1 + 0.378X2 + e. The t test computation's results indicate that there is a partial positive relationship between the Promotion variable (X1) and rising sales volume (Y). Partially contributing to the increase in sales volume (Y) is the Buying Interest variable (X2).